Experimental Leakage Analysis for Push Fit Elastomeric Steel Pipe Spigot and Socket Joint - Abdul Aziz, Faieza (2002)
Pipes have been used for many centuries for transporting fluids. Steel is one of the most versatile materials for pipe walls, as it is ductile yet has a high tensile strength. Steel pipes are made in lengths of up to 10m and jointed on site. Several pipes need to be joined to form a piping system. The type of joint to use on a pipeline will depend on the type of pipe materials, strength and flexibility requirement, cost, water tightness and the facilities available on site. Currently used joints for large diameter steel pipes are welded sleeve (i.e. spigot and socket), mechanical, flanged and butt welded joints. This research is carried out to investigate the capability of the elastomeric ring as a seal for large diameter steel pipe joint. A pair of spigot and socket pipe with a mean outer diameter of 668 mm is being used in this project. A socket pipe which has groove for elastomer location has an inner diameter of 690.2 mm while spigot pipe which has tapered part having outer diameter of 654 mm at its end. An elastomeric lip seal of dual hardness which is having 702 mm outer diameter is also being used in this work. The technique of push-fit method has yet to be introduced as an alternative joining method for larger steel pipes to quicken and ease the process. An experimental test rig is designed and fabricated to test the performance of the joint as in working environment. Two type of tests are conducted - pressure test and leakage test. The findings indicated that the water pressure inside the pipe is 0.625 MN/m2, lower than the contact pressure exist at the top and bottom surfaces of elastomer that are 28.541 MN/m2 and 23.758 MN/m2 respectively. The results of pressure test shows that no leaking occurs along the test including the extension of 10 minutes after full pressure test has been attained. The leakage test is also success as no water is added/pumped to maintain the pressure of 4.17 bar for a period of 24 hours.